Magnetic field strength of a neutron-star-powered ultraluminous X-ray source. (April 2018) - Brightman, M.; Harrison, F.; Fürst, F.; Middleton, M.; Walton, D.; Stern, D.; Fabian, A.; Heida, M.; Barret, D.; Bachetti, M.
Abstract Ultraluminous X-ray sources (ULXs) are bright X-ray sources in nearby galaxies not associated with the central supermassive black hole. Their luminosities imply they are powered by either an extreme accretion rate onto a compact stellar remnant, or an intermediate mass ( 100–105 M ⊙ ) black hole1 . Recently detected coherent pulsations coming from three bright ULXs2–5 demonstrate that some of these sources are powered by accretion onto a neutron star, implying accretion rates significantly in excess of the Eddington limit, a high degree of geometric beaming, or both. The physical challenges associated with the high implied accretion rates can be mitigated if the neutron star surface field is very high (1014 G)6, since this suppresses the electron scattering cross-section, reducing the radiation pressure that chokes off accretion for high luminosities. Surface magnetic field strengths can be determined through cyclotron resonance scattering features7, 8 produced by the transition of charged particles between quantized Landau levels. Here, we present the detection at a significance of 3.8σ of an absorption line at 4.5 keV in the Chandra spectrum of a ULX in M51. This feature is likely to be a cyclotron resonance scattering feature produced by the strong magnetic field of a neutron star. Assuming scattering off electrons, the magnetic field strength is implied to be 1011 G, while protons would imply a magnetic field of B 1015 G. The power source of ultraluminous X-ray sources (ULXs) is still debated. A detection of an absorption line at 4.5 keV in the Chandra spectrum of a ULX supports the scenario of a strongly magnetized neutron star accreting at super-Eddington rates.